The transformation of the automotive industry toward electrification and its impact on global value chains: Inter-plant competition, employment, and supply chains - Mario Rísquez Ramos; María Eugenia Ruiz-Gálvez (European Research on Management and Business Economics (ERMBE), 2024)
The automotive industry is undergoing a profound transformation in its transition to production of electric vehicles. This paper seeks to examine the main transformations taking place in global value chains in the automotive industry as a result of this transition. The analysis follows a multiple case study methodology based on a theoretical approach that seeks to address the research question and purpose. The main findings of this research focus on three dimensions of GVCs. First, this transition increases competition among assembly plants at the intra-group level for the awarding of new models. Second, it continues to reconfigure supply chains, threatening the viability of certain traditional providers of components and giving rise to new players - battery manufacturers - that may challenge the chain hierarchy. Third, the transition to electric vehicles has led to a reduction in employment volume in the chain as a whole. Because the transition is ongoing, it will continue to pose significant challenges for multiple actors involved in the automotive industry.
Keywords: L62; L23; L24; O33; 650; Automotive industry; Design for manufacture; Supply chains; Technological change